Litigation Risk as a Moderating Variable of the Influence of Digital Financial Report Quality on Investment Efficiency - Rudi Ginting; Dessy Evianti; Muhammad Yusuf; Lia Nurina; Rieneke Ryke Kalalo (JURNAL ILMIAH EDUNOMIKA, 2025)
Abstract This research is a quantitative study with an explanatory approach, namely an approach that uses a number of previous studies as the main source to further analyze the hypothesis in this study. The data used in this article is secondary data that researchers obtained from employees of PO Rosalia Indah spread across several corners of Indonesia. The data used were analyzed using the smart PLS 4.0 analysis tool. The result in this article show that the Digital Financial Report Quality variable is acceptable, meaning that the variable has a positive relationship direction and a significant influence on Investment Interest. This is because the P-Values ​​are positive and below the significance level of 0.05, namely 0.019. This is because the Digital Financial Report Quality value can make the company's finances stable, transparent, and trusted by many stakeholders which can increase investment interest. In addition, in the next hypothesis, the Litigation Risk variable can moderate the influence of the Digital Financial Report Quality variable on Investment Interest because the P-Values ​​are positive and below the significance level of 0.05, which is 0.000, which is more significant than direct testing of 0.019. Thus, it can be concluded that the first and second hypotheses in this article can be accepted. Keywords :Litigation Risk, Digital Financial Report Quality, Investment Efficiency